Effects of melatonin on oxidative stress parameters and pathohistological changes in rat skeletal muscle tissue following carbon tetrachloride application - Dušan T. Sokolović; Ljubiša Lilić; Vesko Milenković; Rade Stefanović; Tatjana Popović Ilić; Branimir Mekić; Igor Ilić; Nikola M. Stojanović; Ivan R. Ilić (Elsevier, 2018)
Animal models demonstrating skeletal muscle (SM) disorders are rarely investigated, although these disorders accompany liver disorders and can occur during prolonged exercise/training. In cases of SM disorders exogenous antioxidants, such as melatonin, could help by generally improving tissues antioxidant capacities. We aimed to analyze the potential of melatonin in preventing biochemical and structural changes in rat biceps muscle (BM) occurring after an acute exposure to carbon tetrachloride (CCl4). Biceps muscles obtained from male Wistar rats belonging to different experimental groups were biochemically (determination of tissue MDA, total antioxidant capacity, GSH, CAT, SOD and GPx activities) and pathologically analyzed. Also, serum levels of potassium, LHD and CK were analyzed in all experimental animals. The obtained results were statically compared with those from vehicle-treated control group. The applied melatonin prevented potassium and intracellular enzyme leakage (CK and LDH) that was induced by CCl4, as well as an increase in tissue MDA. From a panel of determined oxidative stress parameters melatonin was able to statistically significantly prevent changes in total antioxidative capacity and in CAT, SOD and GPx activities induced by CCl4. Microscopic analysis of BM from the animals exposed to CCl4 revealed significant muscle fiber disorganization and massive inflammatory cell infiltration. All these changes were significantly ameliorated in the group that received melatonin prior to CCl4. Changes in serum and tissue biochemical parameters accompanied the observed pathological changes, which demonstrated a significant influence of melatonin in preventing skeletal muscle damage induced by CCl4. Keywords: Carbon tetrachloride, Melatonin, Skeletal muscles, Oxidative damage